SHORT-TERM OUTCOMES OF LAPAROSCOPIC REMOVAL OF OVARIAN CYSTS IN PATIENTS WITH INFERTILITY USING VARIOUS METHODS OF SURGICAL HEMOSTASIS - Najmutdinova, D.K; Saparov, A.B; Klychev, S.I. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
to study the short-term outcomes of laparoscopic removal of ovarian cysts using different methods of hemostasis (closure, monopolar, bipolar and ultrasound coagulation) in infertility patients. Material and methods: The prospective part of the study included 8 patients with ovarian cysts and infertility, who were operated on laparoscopically in the period from May to September 2018 under conditions of the Department of Gynecology No. 1 of the State Administration of the RSNPMTSAG. Retrospectively, the same criteria were analyzed in 32 patients with infertility, who in the period from 2017 to 2018. laparoscopic removal of ovarian cysts was performed. Results: The use of a combination of mechanical and systemic chemical hemostasis during laparoscopic removal of ovarian cysts in women with infertility does not lead to an increase in the duration of surgical treatment and the volume of intraoperative blood loss. The combination of laparoscopic suturing of the bleeding areas of the bed of the removed cyst with intravenous administration of tranexamic acid does not worsen the course of the postoperative period and does not increase the duration of hospitalization. The use of a combination of mechanical and chemical hemostasis in laparoscopic removal of ovarian cysts in patients with infertility is a good alternative to conventional and widely used methods of hemostasis. Conclusions: it is necessary to conduct further studies to assess the effect of various methods of hemostasis on the ovarian reserve and reproductive outcomes in patients with infertility who underwent laparoscopic removal of ovarian cysts.